Approach to the Status and Management of Languages in the Catalan Public Health Care System - Pere Mas, Jordi (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health.